Masase Kaki Dengan Citronella Oil Terhadap Penurunan Tekanan Darah Pasien Hipertensi Di Wilayah Puskesmas Medokan Ayu Surabaya - Yumni, Fathiya Luthfil; Holidah, Evi Nur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Hypertension is a condition of high blood pressure persistence in vascular blood vessels. Hypertension management consists of two variety, those are: pharmacology and non-pharmacology. In general, people are more consumptive in pharmacology therapy which has bad long-term effect than non-pharmacology therapy which has many advantages and benefits. One of non-pharmacology therapy is foot massage with citronella oil which has relaxation effect and be able to lower blood pressure. Aim of this research was to identification foot massage implementation with citronella oil to lower blood pressure toward hypertension patient in Medokan Ayu Public Health Center, Surabaya. The design of this research used case study to 4 respondents with the criteria of hypertension stadium 1 and do not consume anti-hypertension medicine. This research had been done in Medokan Ayu Public Health Center for 2 weeks. The result showed that after having foot massage for 15 minutes, blood pressure of those 4 respondents were lower in Mr.J amount of 135/88 mmhg and Mrs.S was 130/92 mmhg and majority of the respondents’ response were agreed that they were relax and having sleep well. The conclusion of this research was foot massage with citronella oil can be lower blood pressure toward the hypertension patients. Because of that, hopefully this therapy can be an alternative to lower blood pressure because more safety and have any bad effect even it is in long-term implemented.